Regional Economic Development Strategy - Deffrinica Deffrinica; Helena Anggraeni Tjondro Sugianto; Benedhikta Kikky Vuspitasari (Gorontalo Development Review, 2022)
Regional economic development is development activity carried out by the local government, especially in the Bengkayang Regency area where development is carried out together with the local community, so that the government can manage and utilize existing resources optimally so that the regional economic development of Bengkayang Regency and the welfare of the local community Bengkayang Regency is better. One of the benchmarks for the success of regional economic development and community services in the region can be seen from the regional economic growth. The purpose of this research is to analyze the regional economic development strategies carried out by the Bengkayang Regency Government in increasing the economic growth of Bengkayang Regency so that it can increase the regional development of Bengkayang Regency. This research was conducted for almost one year and used qualitative research methods with a descriptive approach. The results of this study show the development strategies carried out by Bengkayang Regency in accelerating good development and reducing poverty, namely improving the quality of education, improving the quality of health, improving the quality of religious life, improving the quality of governance, improving the quality and quantity of infrastructure, increasing productivity of regional superior sectors, increased village development, increased development of border areas, and increased environmental sustainability.